Convergence of EU-regions: A literature report - Hans-Friedrich Eckey; Matthias Türck (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
Convergence studies are concerned with the question of whether poor economies catch-up to wealthier economies over time. The regional convergence process in Europe has generated considerable interest in recent years. Because of financial straits regional convergence is a central question, since important funds aim at diminishing disparities. There are many studies published recently dealing with this issue using different empirical approaches. Especially the β-convergence framework, which was introduced by Barro and Sala-i-Martin, is often used. This paper provides a critical review of the different approaches and summarizes the results. Altogether it can be stated that most models find a slow convergence - global or only referring to some regions (convergence clubs).
Keywords: O41; R11; R12; 330; Regional Convergence; Literature Report; Europe